The Zelynafah Booster: Leveraging Tiktok for Vocabulary Acquisition with A Quasi-Experimental Study in Indonesian Context - Puspita, Tasya; Wahidah; Afna, Mauloeddin (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2024)
This study investigated the impact of TikTok videos, specifically from the Zelynafah account, on vocabulary acquisition among junior high school students at SMP N 7 Langsa. A quasi-experimental design was employed, comparing an experimental group using TikTok videos with a control group using traditional methods. Data were collected through pre-tests and post-tests administered from July 15 to 24, 2024 with 20 students as the samples of study. The results indicated significant vocabulary improvement in both groups, with the experimental group demonstrating a more pronounced increase. The experimental group's mean score rose from 29.50 to 81.50, compared to the control group's increase from 21.00 to 76.00. Statistical analyses confirmed the effectiveness of the TikTok intervention, with the experimental group exhibiting a larger effect size. Increased student engagement was also observed in the experimental group. These findings suggest that incorporating TikTok videos into language teaching can significantly enhance vocabulary acquisition among junior high school students.